An Analysis of Romantic Partnership Dynamics in Domestic Minor Sex Trafficking Case Files - Twis, Mary K. (Journal of interpersonal violence, 2022)
Domestic minor sex trafficking (DMST) is the commercial sexual exploitation of a minor citizen or legal resident within the United States. Previous research suggests that although DMST is often discussed as though it is a uniform phenomenon, traffickers may use different tactics and exploit different victim vulnerabilities depending upon their established relationships with those who are at-risk for trafficking. The purpose of this qualitative study, therefore, is to explore the relationship patterns and dynamics that emerge between DMST victims and their romantic partner traffickers. This study utilizes the secondary case files of 38 domestic minors who were trafficked for sex by their romantic partners in one state in the United States between 2012 and 2017. The study is conceptualized according to the principles of directed content analysis and multiple case study design and relies heavily on previous research findings related to victim-trafficker relationship typology. The authors conducted two rounds of coding before applying themes to the case files. The analysis revealed that DMST victims trafficked by romantic partners are often influenced by environmental circumstances, such as gang involvement and family systems involvement. Romantic partner traffickers use specific recruitment tactics to entrap their victims, and exercise methods such as caregiving, sexual violence, and psychological violence to maintain control over their victims. Study results provide a significant extension to the anti-trafficking field?s understanding of DMST and the romantic partner relationships that underpin it. The results suggest that anti-trafficking advocates should screen at-risk adolescents for gang involvement, family involvement in the sex industry. They should also educate at-risk adolescents about DMST as a potential component of teen dating violence.